Fluid catalytic cracking handbook design, operation, and troubleshooting of FCC facilities - Sadeghbeigi, Reza. (Houston : Gulf, 2000)
This thoroughly updated edition of Fluid Catalytic Cracking Handbook provides practical information on the design, operation, troubleshooting, and optimization of fluid catalytic cracking (FCC) facilities. Based on the author's years of field experience, this expanded, second edition covers the latest technologies to improve the profitability and reliability of the FCC units, and provides several "no-to-low-cost" practical recommendations. A new chapter supplies valuable recommendations for debottlenecking and optimizing the performance of cat cracker operations.
Process description -- FCC feed characterization -- FCC catalysts -- Chemistry of FCC reactions -- Unit monitoring and control -- Products and economics -- Project management and hardware design -- Troubleshooting -- Debottlenecking and optimization -- Emerging trends in fluidized catalytic cracking.
Includes bibliographical references and index.
Keywords: Catalytic cracking; Craquage catalytique; Electronic books